2012
DOI: 10.1590/s0104-64972012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Range extensions along western Atlantic for Epialtidae crabs (Brachyura, Majoidea) genera Acanthonyx Latreille, 1828 and Epialtus H. Milne Edwards, 1834

Abstract: The present study provided information extending the known geographical distribution of three species of majoid crabs, the epialtids Acanthonyx dissimulatus Coelho, 1993, Epialtus bituberculatus H. Milne Edwards, 1834, and E. brasiliensis Dana, 1852. Specimens of both genera from different carcinological collections were studied by comparing morphological characters. We provide new data that extends the geographical distributions of E. bituberculatus to the coast of the states of Paraná and Santa Catarina (Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…This spider crab has a sharp dactyl curved inward on each pereiopod, which provides better grip onto the seaweed and prevents dislodgement by the force of water (Castaño and Campo, 2003). On the Atlantic coast, E. brasiliensis are distributed from northern Florida, USA to the Rio Grande do Sul, southern Brazil (Rathbun, 1925;Tamburus and Mantelatto, 2012). Reports have shown that these spider crabs are preyed upon by rocky shore fish, such as Stephanolepis hispidus Linnaeus, 1766 (Dubiaski-Silva andMasunari, 2008) and octopus Octopus insularis Haimovici, 2008 (Batista andLeite et al, 2016).…”
Section: Epialtus Brasiliensis Associated With Seaweedmentioning
confidence: 99%
“…This spider crab has a sharp dactyl curved inward on each pereiopod, which provides better grip onto the seaweed and prevents dislodgement by the force of water (Castaño and Campo, 2003). On the Atlantic coast, E. brasiliensis are distributed from northern Florida, USA to the Rio Grande do Sul, southern Brazil (Rathbun, 1925;Tamburus and Mantelatto, 2012). Reports have shown that these spider crabs are preyed upon by rocky shore fish, such as Stephanolepis hispidus Linnaeus, 1766 (Dubiaski-Silva andMasunari, 2008) and octopus Octopus insularis Haimovici, 2008 (Batista andLeite et al, 2016).…”
Section: Epialtus Brasiliensis Associated With Seaweedmentioning
confidence: 99%
“…Distribuição. Atlântico Ocidental: Brasil (Maranhão até São Paulo) (Coelho & Torres, 1993;Melo, 1996;Coelho et al, 2008) e México (presente estudo; Tamburus & Mantelatto, 2012) (Fig.3).…”
Section: Descriçãounclassified
“…Chile (?) (Rathbun 1925(Rathbun , 1933Abele & Kim, 1986) ou proveniente do Atlântico (Garth, 1958 (Coelho, 1971;Powers, 1977;Coelho et al, 1986;Melo, 1996;Hernández-Aguilera et al, 1997;Marcano & Bolaños, 2001;Hernández-Ávila et al, 2007;Coelho et al, 2008;Felder et al, 2009;Lima Júnior et al, 2010); Brasil, distribuição ampliada para Paraná e Santa Catarina (Tamburus & Mantelatto, 2012; presente estudo); Porto Rico (Rathbun, 1933), Panamá (Caribe) (Powers, 1977), Belize, Costa Rica (Tamburus & Mantelatto, 2012;presente estudo) e Chile (Garth, 1958) (Fig. 9).…”
Section: Epialtus H Milne Edwards 1834unclassified
See 2 more Smart Citations